NGOs, from the Promotion of Civic Participation to Public Problems Solving - Kamran Golmohammadpoor Azar; Amin Banae Babazadeh (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In the contemporary world, NGOs are considered as important tool for motivating the community. So they committed their true mission and the promotion of civic participation and strengthen social identities. Functional characteristics of non-governmental organizations are the element to leverage the centers of political and social development of powerful governments since they are concrete and familiar with the problems of society and the operational strategies which would facilitate this process of mutual trust between the people and organizations. NGOs on the one hand offer reasonable solutions in line with approved organizations as agents to match between the facts and reality of society and on the other hand changes to a tool to have true political, social and economical behavior. However, the NGOs are active in the formulation of national relations and policy formulation in an organized and disciplined based on three main factors, ie, resources, policies, and institutions. Organizations are not restricted to state administration in centralized system bodies and this process in the democratic system limits the accumulation of desires and expectations and at the end reaches to the desired place. Hence, this research will attempt to emphasis on field research (questionnaire) and according to the development evolution and role of NGOs analyze the effects of this center on youth. Therefore, the hypothesis is that there is a direct relationship between the Enlightenment and the effectiveness of policy towards NGOs and solving social damages.
Conference: The First International Conference on Political Epic (With an Approach to the Middle East Developments) & Economic Epic (With an Approach to Management and Accounting), February 13th-14th, 2014, Rudehen Islamic Azad University, Iran
Keywords: O15; L30; L31; L38; 330; NGO; Insightful; Civic Participation; Community Vulnerability